Art work seeing inside the creative process - Vartanian, Ivan.; Frere-Jones, Sasha; Parker, Justine (San Francisco, Calif. Chronicle Books, 2011)
"Art work grants rare access to the notebook pages and other visual materials used by more than twenty artists in the exploration and creation of their work"--[P.] 4 of cover.

From actual notebooks to a blizzard of port-it notes to the marks left on the walls of a sculptor's studio, art work collects and explores the physical records of creative thinking. Focusing on creators from a range of disciplines--including photography, dance, sculpture, fiction, and film--each profile includes a generous visual survey of materials generally not meant for public display, as well as essays and notes that together offer an illuminating and inspiring look at the artistic mind at work.
Donated by Prof. Michelle Roxas
Keywords: Artists; Art -- Technique